Are S1 Screws a Useful Adjunct to Iliac Screws in Long Fusions to the Sacrum in Cerebral Palsy?. Issue 2 (January 2016) - Schoenleber, Scott J.; Asghar, Jahangir; Bastrom, Tracey P.; Shufflebarger, Harry L.; ,
Abstract : Study design: Multicenter prospective database review of patients with cerebral palsy (CP) and spinal deformity. Objective: To determine if the type of distal fixation is associated with improved correction of coronal deformity or pelvic obliquity (PO) at 2 years in long posterior fusions to the sacrum. Summary of background data: Multiple techniques are utilized for distal fixation in patients with CP. Although there is emerging evidence that the augmentation of iliac screws with S1 screws may be beneficial, this remains controversial. Methods: A prospective, multicenter database was used to identify patients with CP who underwent long posterior fusions to the sacrum. Eighty-eight patients were included, 52 with iliac screws (I) and 36 with iliac and S1 screws (IS) for distal fixation. Preoperative, first erect, and 2-year follow-up radiographs and complications were analyzed. Statistical analysis was performed using ANOVA and repeated measures ANOVA with significance set at P < 0.05. Results: Scoliosis was the primary deformity in greater than 90% of patients in both groups ( P =0.84). Preoperative coronal deformity was similar (I = 83°, IS = 87°, P = 0.49), but correction was better with the use of S1 screws on the first erect radiograph and at 2 years (I = 35°, IS = 22°, P = 0.001), reflecting correction of 58% and 74% for iliac and iliac-S1 screws, respectively ( P < 0.001). Preoperative PO was similar (I = 29°, IS = 30°, P = 0.71) and was noted to improve more in the iliac-S1 group by 2 years (I = 11°, IS = 5°, P = 0.004), representing correction of 60% and 77% for the iliac and iliac-S1 groups, respectively ( P = 0.018). There was no difference in the rate of major ( P = 0.27) or minor ( P = 0.65) complications in either group. Conclusion: Bilateral S1 and iliac screws are associated with improved spinal deformity and PO correction at 2 years in the CP population. Two points of distal fixation, S1, and ilium should be considered for this population. Level of Evidence: 3